2010
DOI: 10.1111/j.1365-2516.2009.02167.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of chromosomal breakages after radioisotope synovectomy for treatment of target joints in patients with haemophilia

Abstract: Radioisotope synovectomy (RS) is defined as the intra-articular injection of radioisotopic agents with the aim of fibrosis on hypertrophic synovium in the target joint. The aim of this study was to investigate genotoxic effects on lymphocytes and malign transformation induced by Yttrium(90) (Y(90)) and Rhenium(186) (Re(186)) in children with haemophilia undergone RS. Forty haemophilia patients were enrolled. The mean age was 16.4 +/- 6.2 years (range: 8-40). Y(90) was used for knees, Re(186) was used for other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…138 Radiation synovectomy is complicated by rare cutaneous radiation necrosis 67 and concerns about genotoxic effects. 68 …”
Section: Intra-articular Therapeuticsmentioning
confidence: 99%
“…138 Radiation synovectomy is complicated by rare cutaneous radiation necrosis 67 and concerns about genotoxic effects. 68 …”
Section: Intra-articular Therapeuticsmentioning
confidence: 99%
“…32 P has not been approved by European Medicine Agency (EMA) for European countries yet. In our country, due to unavailability of 32 P in the market, we have never used this agent for Turkish patients just like other European centers [8].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, we have studied the effect of RS procedure in patients with hemophilia before and after the therapy [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the chromosomal changes after RS, several authors have shown that genotoxic radiation doses delivered to the peripheral lymphocytes are not statistically significant (17,18,19,20,21). However, transient increase in micronuclei of peripheral lymphocytes may be expected soon after Y-90 therapy which disappeared at 90 th .…”
Section: Introductionmentioning
confidence: 99%